An assessment of parents' childhood immunization beliefs, intentions, and behaviors using a smartphone panel. Issue 10 (28th February 2020) - Boyle, John; Berman, Lew; Nowak, Glen J.; Iachan, Ronaldo; Middleton, Deirdre; Deng, Yangyang
Abstract: Introduction: It is important to quickly identify parent beliefs, intentions, and behaviors toward childhood vaccination, especially parents of children 19 to 35 months. This paper describes parental immunization beliefs, intentions, and behaviors; assesses the relationships between beliefs and intentions regarding child immunization and actual behaviors; and assesses whether beliefs, intentions, and/or behaviors varied across demographic subgroups. Methods: A sample of parents, ages 18 and older, from a mobile panel with people residing in the U.S. were invited to answer immunization behavior, intention, and belief questions using a smartphone app that was not vaccine specific. 10, 000 panel members with a child under 18 were sent invitations. 1029 surveys were completed by a respondent with a child 19 to 35 months. The survey instrument replicated many NIS questions and had similar sequencing. Findings: Respondents reported that most children received all recommended vaccines, except flu vaccine, suggesting some may not understand the immunization schedule. Demographics closely associated with immunization behaviors were respondents' education and household income. There is strong agreement that vaccines are effective, important to community health, and the child's health. There is concern about the number of shots received, disease prevention, and ingredient safety. Some belief remains about vaccines causing learning disabilities. Positive beliefs about the benefits of childhood vaccines and concomitant risks vary with demographics. Conclusions: This survey provided insights into beliefs and behaviors of parents regarding childhood vaccination. It found evidence of differences in beliefs, particularly related to delaying or declining recommended childhood vaccinations. The survey was conducted in a few days and at lower cost than traditional methods. This serves as a model for health agencies where rapid results or inexpensive approaches are needed.